MEDIA RELATIONS STRATEGY OF JOMBANG DISTRICT GOVERNMENT PR IN IMPLEMENTING PUBLICITY DURING THE COVID-19 PANDEMIC - Frida Ainun Rosyidah; Diana Amalia (Universitas Islam Balitar, 2022)
Building a media relations strategy to achieve agency publicity is carried out by the Jombang Regency Government Public Relations to carry out cooperative relationships with the mass media, especially during the COVID-19 pandemic. The public needs to know information about COVID-19 updates and government programs in order to get accurate and reliable information from the source. This study aims to determine the media relations strategy of the Jombang Regency Government Public Relations in carrying out publicity during the pandemic. This research method uses qualitative research with descriptive analysis. The technique used in data collection is in two ways, namely in-depth interviews, and documentation. The results of this study explain that the Jombang Regency Government Public Relations during the COVID-19 pandemic has attempted to disseminate and convey information to the public, but its implementation is still not optimal, because there are obstacles such as: (a) Limited information in accessing technology in some areas. the Jombang community. (b) There are media that take advantage of the news of the COVID-19 pandemic situation. Therefore, the Public Relations of the Jombang Regency Government set a special strategy in conducting media relations, namely managing relationships, develop strategy and develop networks. The purpose of this strategy is to support the public relations tasks of the Jombang Regency Government Public Relations in reaching out to the entire community.